The Qibla: An Allusion to the Shema’ - Galadari, Abdulla (Comparative Islamic Studies, 2016)
In this article it is argued that the Qiblah passages in the Qur’an, which are commonly understood as referring to the direction of the prayer, are directly engaging with and interpreting the Shema passages in Deuteronomy and their Talmudic commentaries. By defining and applying the method of intertextual polysemy, nine points of intertextuality are identified between the various Qur’anic, Biblical, and Talmudic passages. Against this background, the article implies that narrations from traditional Qur’anic commentaries are lacking in their interpretation of these passages, since they do not employ any extra-Quranic contexts to explain their meaning. Through the method of intertextual polysemy, the alternative thesis propounded here is that the historical reference for the Qiblah passages is the Shema.